The Development of A Flexible Battery by Using A Stainless Mesh Anode - Kanawe Iwai; Teppei Tamura; Dang-Trang Nguyen; Kozo Taguchi (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
We have developed a compact and flexible battery, which composes three parts: (1) an anode electrode made for stainless mesh which was heat-treated for 30 min at 500℃ with coated carbon nanotube (CNT), (2) a piece of paper filter-based membrane with the pore size of 0.025 µm and the thickness of 100 µm, and (3) a cathode electrode coated potassium ferricyanide. The battery can generate electricity activated by adding sodium chloride (NaCl) solution to the anode. The battery has a NaCl concentration-dependence characteristic. In this research, we tested 0.5, 1, 3, 5, and 10% NaCl solution, respectively. At 3% NaCl concentration, the maximum power density and current density of 42.3 µW/cm2 and 228 µA/cm2 were obtained, respectively. After the experiments, there was a blue material encountered on the anode surface. By using EDS to analyze the blue material, it could be confirmed that the blue material was ferric ferrocyanide (Prussian blue). The operation principle of this battery was proposed as follows. First, on the anode side, the injected sodium chloride solution oxidizes the stainless mesh surface, then ferric ions and electrons are released. Second, on the cathode side, ferricyanide ions are reduced to ferrocyanide ions by electrons coming from the anode through the external circuit. Simultaneously, ferric ions react with ferrocyanide ions to produce Prussian blue and generate more electrons. This battery can be potentially utilized for applications that require on-demand, disposable, and flexible characteristics. ©2019. CBIORE-IJRED. All rights reserved